Risk Perceptions of Insurance Policyholders in the Gauteng Region of South Africa - Suné Ferreira-Schenk; Zandri Dickason-Koekemoer; Marko Van Deventer (Acta Economica)
The insurance industry’s product range is diverse, and the risk perception of each product differs from that of insurers, especially given the constantly changing market conditions. Often, insurance companies misunderstand the risk perceptions of their policyholders and inevitably lose clients. To better understand these perceptions of risk, this paper aims to analyze the endogenous factors that influence the perception of risk of insurance policyholders in Gauteng, South Africa. These endogenous factors include demographics, risk perception, risk tolerance, and behavioral finance biases. South African insurance policyholders residing in Gauteng province of South Africa were identified as the target population for this study. From this study, endogenous factors such as age, health status, representativeness, and availability bias, as well as self-control, were identified as significant factors influencing the risk perception of insurance policyholders. The risk tolerance profile of the sample indicated that most participants would take average financial risks as most assets were covered, but not comprehensively. Risk tolerance was also found to be a contributing factor to the risk perception of policy holders. By gaining deeper insights into insurance policyholder risk perceptions and the antecedents thereof, insurance companies could be better position to expand their horizons and provide higher quality insurance services to their clients.